2018
DOI: 10.1097/sap.0000000000001225
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Versus Pure Variants of Desmoplastic Melanoma

Abstract: Pure and mixed DMs seem to have similar clinical characteristics and outcomes. This indicates that analysis of national datasets without this subclassification remains viable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 17 publications
3
24
1
Order By: Relevance
“…In this study, we found an overall SLNB positivity rate of DM of 9.7% in 62 SLNBs. This is comparable to previous studies with rates ranging from 0% to 18.2% . The sample size in these studies varied from 12 to 505 patients who underwent SLNB, which might account for the wide range of SLNB positivity rates found.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…In this study, we found an overall SLNB positivity rate of DM of 9.7% in 62 SLNBs. This is comparable to previous studies with rates ranging from 0% to 18.2% . The sample size in these studies varied from 12 to 505 patients who underwent SLNB, which might account for the wide range of SLNB positivity rates found.…”
Section: Discussionsupporting
confidence: 86%
“…When comparing MDM to PDM in the current study, 6/36 (16.7%) of patients with MDM had a positive SLNB and 0/26 (0%) of the patients with PDM ( P = .0035). In earlier studies with more than 25 SLNBs, positivity rates of MDM ranged from 8.5% to 24.6% and of PDM from 2.2% to 18.2% . All but one study found lower rates for PDM compared to MDM .…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations